PENGARUH DINASTI AL SA’ID TERHADAP SEJARAH PERADABAN OMAN - Budi Darmawan; Faras Puji Azizah (RUSYDIAH: Jurnal Pemikiran Islam, 2023)
This article studies various things that happened and existed in the Sultanate of Oman, starting from the pre-Islamic period to the modern period, especially during dinasty Al Sa’id, because it has become an important area for the West Asia region, especially during the time of Sultan Qaboos, where Oman experienced progress and liberalization on many sides such as economy, culture, and others. The method used is the historical method by performing several stages such as heuristics, source criticism, synthesis, and finally writing or historiography. The results of this research are, Oman is an important port country, especially for West Asian countries, since the time of ancient Oman. from the coastal areas of Oman, the distribution of various cultures from various worlds, and spread to mainland West Asia. Judging from the significance of Oman for West Asian countries, it is important for us to be able to see and examine what has happened in Oman in the development of its civilization, both in terms of economy, culture, religion, politics, or even from its history.